Vitamin D, insulin-like growth factor-1, and stunting in children with transfusion-dependent thalassemia - I Gusti Ayu Putu Eka Pratiwi; Roedi Irawan; I Dewa Gede Ugrasena; Muhammad Faizi (Paediatrica Indonesiana, 2022)
Background Transfusion-dependent thalassemia (TDT) has a major impact on a child's growth and is associated with stunting, risk of vitamin D deficiency, and decreased insulin-like growth factor-1 (IGF-1). To date, the relationship between vitamin D levels and stunting in TDT remains unclear. Futhermore, the role of vitamin D and IGF-1 in mediating stunting in TDT patients is still unknown. Objective To investigate the relationship between stunting and vitamin D as well as IGF-1 levels in children with TDT. Methods This cross-sectional study involved 50 TDT children aged 5 to 18 years, included consecutively from the Pediatric Hemato-oncology Outpatient Clinic, Dr. Soetomo Hospital, Surabaya, East Java. Subjects were divided into two groups: stunted (S) and not stunted (NS). Vitamin D and IGF-1 were evaluated by antibody competitive immunoassay and sandwich-enzyme-linked immunosorbent assay (ELISA), respectively. Age, sex, and duration of repeated transfusion were analyzed as confounding factors. Results Median IGF-1 levels were 91.43 (13.67-192.86) ng/mL and 161.53 (17.99-363.01) ng/mL in the S and NS groups, respectively (P=0.011). Mean vitamin D levels were 20 (+ 5.71) ng/mL and 20.46 (5.25) ng/mL in the S and NS groups, respectively (P=0.765). The correlation coefficient (r) of vitamin D and IGF-I levels was not significant. Multivariate analysis showed that low IGF-1 levels, male, and longer duration of repeated transfusions were associated with stunting in children with TDT. Conclusion Low IGF-1 level is associated with stunting in children with TDT. Vitamin D is not significantly associated with either stunting or IGF-1 in children with TDT.